Odpowiedź:
f(0) = [tex]3^0 - 2 = 1 - 2 = - 1[/tex] A =( 0, -1)
f(1) = [tex]3^1 - 2 = 3 - 2 = 1[/tex] B =( 1, 1 )
f(2) = [tex]3^2 - 2 = 9 - 2 = 7[/tex] C = ( 2, 7)
f (-1) = [tex]3^{-1} - 2 = \frac{1}{3} -2 = - 1 \frac{2}{3}[/tex] D = ( - 1, - 1 [tex]\frac{2}{3}[/tex] )
f ( - 2) = [tex]3^{-2} -2 = \frac{1}{9} - 2 = - 1 \frac{8}{9}[/tex] E = ( - 2, - 1 [tex]\frac{8}{9}[/tex] )
Wykres funkcji wykładniczej przechodzi przez punkty: E, D, A, B , C
Równanie asymptoty poziomej:
y = - 2
=======
ZW = ( - 2 ; + ∞ )
=================
Szczegółowe wyjaśnienie: